Digital Transformation of Islamic Preaching in Kazakhstan: Identifying Famous Online Preachers and Their Influence - Kerim, Shamshadin; Kurmanaliyev, Maxat; Ongar, Yershat; Kaliyeva, Yeleukhan (Millah: Journal of Religious Studies, 2025)
The digital landscape in Kazakhstan has witnessed a notable rise in religious sermons particularly Islamic fueled by the efficiency of social media in rapidly disseminating content and shaping religious beliefs. Social media has become a pivotal medium for the spread of religious teachings, enabling interactive engagement and fostering online faith communities. This shift has expanded access to spiritual knowledge, while also prompting a reassessment of traditional religious authority as new voices emerge. This article seeks to identify key Islamic preachers in Kazakhstan, examine the factors behind their popularity, and conduct a content analysis to evaluate the opportunities and risks associated with online preaching on social media platforms. The study employed both quantitative and qualitative methods. The empirical component involved a survey to pinpoint prominent Islamic preachers in Kazakhstan, alongside content analysis to determine the elements contributing to their widespread appeal. The research identified five influential internet preachers in Kazakhstan, each commanding an audience of over 500,000 subscribers. Their popularity is largely due to a systematic approach, diverse content ranging from foundational beliefs to contemporary societal issues, interactive communication with followers, and distinct personal styles. This study fills a critical gap in the literature by offering a new, data-driven analysis of the growing trend of online Islamic preaching in Kazakhstan. While the digital transformation of religious discourse is a recognized global phenomenon, this research distinguishes itself by focusing specifically on Kazakhstan’s unique socio-cultural and religious context where Islamic tradition intersects with rapid digital adoption, a dynamic that remains largely understudied.